OPTIMALISASI PENDAFTARAN LEGALITAS TANAH WAKAF - Nurum, Munawir (STAI YAPIS Takalar, 2022)
Study this aim for dig problem related registration legality soil waqf in the District Tompobulu , Regency Gowa . Because based on waqf data there are 95 locations waqf , by whole waqf made the object is waqf soil and part big waqf soil the not yet certified as legality soil waqf . Method study this is study qualitative , using field data ( field research ), approach study use approach law and approach sociological . Method manipulation and data analysis was performed with method data reduction , data display and withdrawal conclusion . Based on results research , author conclude that protracted factor back low registration legality waqf is lack of understanding and knowledge law Public as well as paradigm waqf society . So that strategy optimization registration legality soil waqf conducted with build awareness law society , because awareness law will make Public will obey to law .